A repatriação de refugiados afegãos: do Paquistão ao leste do Afeganistão - Candido, Mônica Tse [UNESP] (2014)
The repatriation of Afghan refugees since 2002 was the main operation of this kind in United Nations High Commissioner for Refugees’ (UNHCR) history. Considering this, the present studies discuss the voluntary repatriation programme from 2002 until 2013, as well as the durable solutions model implemented by UNHCR of local integration, resettlement and repatriation. Moreover, it presents the causes of displacement of these refugees to Pakistan, main country of asylum, and the conditions of return to the Eastern region of Afghanistan, bordering area with Pakistan. After return, the main challenges faced by returnees for reintegration in the country of origin are identified and the perspectives from 2014 on, considering the political transition context that Afghanistan is going through.